Stabilization of carbon dioxide and chromium slag via carbonation. Issue 16 (18th August 2017) - Wu, Xingxing; Yu, Binbin; Xu, Wei; Fan, Zheng; Wu, Zucheng; Zhang, Huimin
ABSTRACT: As the main greenhouse gas, CO2 is considered as a threat in the context of global warming. Many available technologies to reduce CO2 emission was about CO2 separation from coal combustion and geological sequestration. However, how to deal with the cost-effective storage of CO2 has become a new challenge. Moreover, chromium pollution, the treatment of which requires huge energy consumption, has attracted people's widespread attention. This study is aimed to develop the sequestration of CO2 via chromium slag. A dynamic leaching experiment of chromium slag was designed to testify the ability of CO2 adsorption onto chromium slag and to release Cr(VI) for stabilization. The results showed that the accumulative amounts of Cr(VI) were ca. 2.6 mg/g released from the chromium slag after 24 h of leaching. In addition, ca. 89 mg/g CO2 was adsorbed by using pure CO2 in the experiment at 12 h. Calcite is the only carbonate species in the post-carbonated slag analyzed by powder X-ray diffraction and thermal analysis. The approach provides the feasibility of the utilization of chromium slag and sequestration of the carbon dioxide at the same time at ordinary temperatures and pressures.